Pengaruh Penggunaan Media Pembelajaran E-Book (Flif Book Maker) Terhadap Minat Belajar Siswa pada Mata Pelajaran Ilmu Pengetahuan Alam di SMP Negeri 1 Cilebak - Masluhin, Uhin; Zakaria, Yoyo (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Learning media is one of the means that can increase the effectiveness and efficiency of teaching and learning activities. The purpose of this study is to determine the effect of the use of e-book learning media (flif book maker) on students' interest in learning in Natural Sciences subjects at SMP Negeri 1 Cilebak. This study uses a quantitative research method with an experimental quasy type. The sample in this study is class VIII-A as many as 21 students as a control class or a class that is not given treatment with a preetest and class VIII-B as an experimental class as many as 21 students or a class that is given treatment and given a posttest. The data collection techniques used are prettest, posttest, and questionnaire questions. The results of hypothesis testing using the N-gain test were obtained with an average value of 71.9048 increase in the experimental group while the increase in the control class was 54.7619 so that it was known that the increase in the learning outcomes of the experimental class was 17.14286 compared to the control class. This study concludes that there is a significant influence between the learning process using conventional methods and learning using E-book media (Flipbook Maker) on students' learning interest